Changes in surface characteristics of titanium and zirconia after surface treatment with ultraviolet light or non‐thermal plasma. (16th January 2018) - Henningsen, Anders; Smeets, Ralf; Heuberger, Roman; Jung, Ole T.; Hanken, Henning; Heiland, Max; Cacaci, Claudio; Precht, Clarissa
Abstract : Positive effects of irradiation with ultraviolet (UV) light or treatment with non‐thermal plasma on titanium and zirconia surfaces have been described in various studies. The aim of this study was to assess and compare the changes in the physicochemical surface conditions of titanium and zirconia surfaces after a short treatment with UV light or with non‐thermal plasmas of argon or oxygen. Titanium and zirconia samples with moderately rough surfaces were treated for 12 min either in a UV‐light oven or in a non‐thermal plasma reactor that generates non‐thermal plasmas of oxygen or argon. Changes in surface conditions were assessed by confocal microscopy, dynamic contact angle measurement, and X‐ray photoelectron spectroscopy (XPS). No changes in roughness occurred. Ultraviolet irradiation and non‐thermal plasma significantly increased the wettability of the titanium and zirconia surfaces. X‐ray photoelectron spectroscopy showed an increase of oxygen and a significant decrease of carbon after treatment with either method. Thus, ultraviolet light and non‐thermal plasma were found to be able to improve the chemical surface conditions of titanium and zirconia following a short exposure time. However, further in vitro and in vivo studies are needed to determine the relevance of the results.